The Career Advancement Experiences of Female Faculty of Color in Athletic Training Education Programs - Carrie Graham; Alexandra Bell (Adult Education Research Conference, 2016)
Healthcare professions are currently experiencing increased professional member diversity, necessitating an investigation of employee workplace experiences and career advancement. Yet, the rate of female faculty of color in athletic training education programs is inconsistent with athletic training membership diversity rates. This study explores their career advancement and mentoring experiences.
Keywords: female faculty of color; microaggressions; mentoring; career advancement